NUMBER OF FAMILY MEMBERS AND FAMILY BUSINESS STATUS EXPLAINED THE LEADERSHIP POSITION IN COMMUNAL ACTIVITY OF FOOD PROCESSING ENTREPRENEUR FOR POVERTY ERADICATION IN RURAL MALAYSIA - Z., Zumilah,; M., Jariah; I, Norisma Aiza (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
A total of 735 rural entrepreneurs were selected and sub sampled from 2,093 rural enterprises of Women ExtensionÂ Group (KPW) under the governance of Malaysia Department of Agriculture (DOA). They are producing processedÂ food products, which is a popular industry to eradicate rural feminism poverty. The main objective of this paper is toÂ explore the leadership positions of rural entrepreneurs in communal activity in relation with type of business ownership.Â Then, follows by identifying factors explain the active group of entrepreneurs in communal activities. To summarize,five types of community activities were traced â politics, religion, community, socio-economy and parent and teacherÂ association (PIBG). The leadership score for entrepreneurs in company was high for political activity, while forentrepreneurs in all other types of business ownership their leadership scores were high in socio-economic activity.Â By sex of entrepreneurs, it may be concluded that entrepreneurs who usually have a leadership position in politicalÂ activities have a tendency to develop their enterprise. By dividing leadership score into two groups â active and lessÂ active, as dependent variable; against gender, family business status, size of business,registration status and numberÂ of family members, as independent variables; Binary Logistic Regression obtained (p<0.05) that an active group canÂ be explained by number of family members and family business status. Every one additional family member mayÂ decrease about 36.1% the likelihood of one respondent in this study to be in active group. Despite offering opportunityfor networking, leadership positions require a lot of time and high commitment. For rural women with many childrenÂ under their care, to active in communal activities is almost inconceivable. Non-family business status may reduceÂ about 37.6% likelihood of one respondent in this paper to be in active group. Thus, especially for rural womenÂ enterprises, they had to operate in form of family business to success. Family business status may reflect potential ofÂ development in rural women business, which is good for family business development. No significant relationshipÂ between other dependent variables with the likelihood of the respondent to be in active group level in this study.